(untitled) (Physical Education, Health and Social Sciences, 2025)
This study looks at the level of knowledge about Basic Life Support (BLS) among undergraduate nursing students at private colleges in Peshawar, Pakistan. BLS is a crucial skill for healthcare workers, especially in emergency situations where quick action can make a life-or-death difference. The goal of this research is to assess how prepared nursing students are to perform BLS and to pinpoint areas where their training could be improved